Optimization of a microchip electrophoresis method with electrochemical detection for the determination of nitrite in macrophage cells as an indicator of nitric oxide production - Siegel, Joseph M. (Anal Methods, 2018)
Nitric oxide (NO) is involved in many biological functions, including blood pressure regulation, the immune response, and neurotransmission. However, excess production of NO can lead to the generation of reactive nitrogen species and nitrosative stress and has been linked to several neurodegenerative diseases and cardiovascular disorders. Because NO is short-lived and generally difficult to detect, its primary stable degradation product, nitrite, is frequently monitored in its place. In this paper, an improved method using microchip electrophoresis with electrochemical detection (ME-EC) was developed for the separation and detection of nitrite in cell lysates. A separation of nitrite from several electroactive cell constituents and interferences was optimized, and the effect of sample and buffer conductivity on peak efficiency was explored. It was found that the addition of 10 mM NaCl to the run buffer caused stacking of the nitrite peak and improved limits of detection. A platinum black working electrode was also evaluated for the detection of nitrite and other electroactive cellular species after electrophoretic separation. The use of a modified platinum working electrode resulted in 2.5-, 1.7-, and 7.2-fold signal enhancement for nitrite, ascorbic acid, and hydrogen peroxide, respectively, and increased the sensitivity of the method for nitrite twofold. The optimized ME-EC method was used to compare nitrite production by native and lipopolysaccharide-stimulated RAW 264.7 macrophage cells.